Network forensics: detection and mitigation of botnet malicious code via darknet - R. Othman, R. Azrina; A. Aziz, Normaziah (Atlantis Press, 2012)
Computer malwares are major threats that always find a way to penetrate the network, posing threats to the confidentiality, integrity and the availability of data. Network-borne malwares penetrate networks by exploiting vulnerabilities in networks and systems. IT administrators in campus wide network continue to look for security control solutions to reduce exposure and magnitude of potential threats. However, with multi-user computers and distributed systems, the campus wide network often becomes a breeding ground for botnets.